PENDIDIKAN MORAL DALAM DRAMA TARTUFFE KARYA MOLIÉRE DAN DRAMA IPHIGENIE AUF TAURIS KARYA GOETHE - Alice Armini (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2013)
This study aims to describe how morality is reflected through the authors’ worldviews in Molière’s drama Tartuffe and Goethe’s drama Iphigenie auf Tauris, with French and German social backgrounds during the classical era. The research data were descriptions of moral education based on the worldviews of the authors of the two dramas. The findings show that the authors’ worldviews are related to universal humanity values. Based on theirworldviews, it can be summarized that the moral education contents in the two dramas are similar, covering sound reasoning, clear mind, and noble character. These three finally succeed in getting rid of human cruelty and uncivilized deeds.